2016
DOI: 10.3389/fnbeh.2015.00369
|View full text |Cite
|
Sign up to set email alerts
|

Extinction and Retrieval + Extinction of Conditioned Fear Differentially Activate Medial Prefrontal Cortex and Amygdala in Rats

Abstract: Pairing a previously neutral conditioned stimulus (CS; e.g., a tone) to an aversive unconditioned stimulus (US; e.g., a footshock) leads to associative learning such that the tone alone comes to elicit a conditioned response (e.g., freezing). We have previously shown that an extinction session that occurs within the reconsolidation window (termed retrieval + extinction) attenuates fear responding and prevents the return of fear in Pavlovian fear conditioning (Monfils et al., 2009). To date, the mechanisms that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…We do not believe this could be the case. Recent studies have indeed shown that post-retrieval extinction engages mechanisms that are distinct from “standard” extinction (Monfils et al, 2009; Clem and Huganir, 2010; Rao-Ruiz et al, 2011; Tedesco et al, 2014; Lee et al, 2016). One explanation of memory updating is that an experience that both evokes a memory for and greatly resembles a previous experience (i.e., possess the same latent causes) is likely to be integrated with the previous memory.…”
Section: Discussionmentioning
confidence: 99%
“…We do not believe this could be the case. Recent studies have indeed shown that post-retrieval extinction engages mechanisms that are distinct from “standard” extinction (Monfils et al, 2009; Clem and Huganir, 2010; Rao-Ruiz et al, 2011; Tedesco et al, 2014; Lee et al, 2016). One explanation of memory updating is that an experience that both evokes a memory for and greatly resembles a previous experience (i.e., possess the same latent causes) is likely to be integrated with the previous memory.…”
Section: Discussionmentioning
confidence: 99%
“…It is especially interesting that adolescent retrieval+ extinction would prevent the recovery of juvenile fears when adult retrieval+extinction on fear memories of similar temporal age fails to attenuate fear (Clem and Huganir 2010;Gräff et al 2014). At the molecular level, retrieval+extinction of a fear memory targets synaptic plasticity within the lateral amygdala where it is hypothesized to destabilize the original memory trace (Monfils et al 2009;Clem and Huganir 2010) by inducing a reconsolidation-like process in the LA, IL, and PRL (Tedesco et al 2014), and engages a mechanism distinct from that involved in standard extinction (Lee et al 2015). This suggests that successful fear reduction with the retrieval+extinction procedure requires destabilization of the memory trace in the LA paired with the incorporation of new information from the PFC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Monfils-Schiller paradigm has been shown to induce neural modifications that are distinct from standard extinction (H. J. Lee, Haberman, Roquet, & Monfils, 2015;Tedesco, Roquet, DeMis, Chiamulera, & Monfils, 2014).…”
Section: Explaining the Mystery Of The Monfils-schiller Paradigmmentioning
confidence: 99%